Haloperidol Plus Ondansetron Versus Ondansetron Alone for Prophylaxis of Postoperative Nausea and Vomiting - Grecu, Loreta; Bittner, Edward A.; Kher, Jay; Smith, Sarah E.; Rosow, Carl E. (Anesthesia and analgesia, 2008)
Haloperidol 1 mg and ondansetron 4 mg are equally safe and effective for postoperative nausea and vomiting prophylaxis. We compared the combination to ondansetron alone in a mixed surgical population. Two-hundred and sixty-eight adults undergoing general anesthesia received 4 mg ondansetron plus 1 mg haloperidol or saline in this randomized, double-blind protocol. Efficacy and safety data were obtained until 480 min after postanesthesia care unit entry. The combination had more complete responders (76.2% vs 59.2%), less nausea, less rescue, and longer time to rescue. Sedation, time to postanesthesia care unit discharge, and QTc prolongation were not different. No subject had dystonia, akathisia, or serious dysrhythmias. Postoperative nausea and vomiting prophylaxis with both drugs is significantly more effective and longer lasting than ondansetron alone. There is no detectable increase in side effects.